Meningkatkan Potensi Desa Darma Melalui Produktivitas Pengembangan Umkm Sebagai Wujud Ekonomi Kreatif - Araniri, Nurudin (Paguyuban Panalungtik Sunda (Papanda), 2022)
Darma village now has several MSMEs already running. but on the other hand, in its implementation there are still obstacles, especially the absence of any form of information from the village that Darma Village has many UMKM products. In addition to the lack of information, UMKM actors in Darma Village are also reluctant to open themselves to advances in digital marketing technology, so digital marketing literacy is needed. The results are as follows:Making UMKM information signs at strategic location points. This program is implemented so that the market share of UMKM players in Darma Village is wider, conducting socialization of the introduction of digital marketing literacy to the community. This activity is carried out so that UMKM actors have insight into digital marketing and MSME actors do not only do conventional marketing but can do it by means of digital marketing; provide insight to the community about hydroponic planting methods so that people can grow crops even with limited agricultural land, for example, such as farming through hydroponic media and polybags.